2014
DOI: 10.1186/1471-2407-14-163
|View full text |Cite
|
Sign up to set email alerts
|

Increasing rates of surgical treatment and preventing comorbidities may increase breast cancer survival for Aboriginal women

Abstract: BackgroundLower breast cancer survival has been reported for Australian Aboriginal women compared to non-Aboriginal women, however the reasons for this disparity have not been fully explored. We compared the surgical treatment and survival of Aboriginal and non-Aboriginal women diagnosed with breast cancer in New South Wales (NSW), Australia.MethodsWe analysed NSW cancer registry records of breast cancers diagnosed in 2001–2007, linked to hospital inpatient episodes and deaths. We used unconditional logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 26 publications
5
68
0
Order By: Relevance
“…two high-quality studies published after 2010 showed a consistent pattern of variations in clinical management, both nationally for 5.4 million women (1% Indigenous; Roder et al, 2012) and at a state-level (n = 27,833, 1% Indigenous; Supramaniam et al, 2014). In particular, Indigenous women were 40% less likely to receive any surgery (Supramaniam et al, 2014), and where surgical management was undertaken, they were more likely to undergo mastectomy rather than complete local excision compared to non-Indigenous women (Roder et al, 2012;Supramaniam et al, 2014).…”
Section: Clinical Managementmentioning
confidence: 88%
See 2 more Smart Citations
“…two high-quality studies published after 2010 showed a consistent pattern of variations in clinical management, both nationally for 5.4 million women (1% Indigenous; Roder et al, 2012) and at a state-level (n = 27,833, 1% Indigenous; Supramaniam et al, 2014). In particular, Indigenous women were 40% less likely to receive any surgery (Supramaniam et al, 2014), and where surgical management was undertaken, they were more likely to undergo mastectomy rather than complete local excision compared to non-Indigenous women (Roder et al, 2012;Supramaniam et al, 2014).…”
Section: Clinical Managementmentioning
confidence: 88%
“…12 months of diagnosis after adjustment for a range of key demographic and clinical factors (Supramaniam et al, 2014). 12 months of diagnosis after adjustment for a range of key demographic and clinical factors (Supramaniam et al, 2014).…”
Section: Recommended Clinical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported ethnic disparities associated with diagnostic delay [71,72]. In Australia, Indigenous women have lower rates of breast screening [13], more extensive disease at diagnosis [73], and less optimal clinical management [74]. While we are unable to assess the exact reasons for the longer diagnostic interval for Indigenous women in our study, it is possible that the differences are caused by issues with accessibility and potentially a lack of culturally sensitive and appropriate health care.…”
Section: Discussionmentioning
confidence: 99%
“…9 13–17 These linkage studies have demonstrated the value of assessing cancer outcomes in relation to patient treatment, comorbidity and various sociodemographic features. Work in New South Wales has compared survival and surgical treatment of Aboriginal and other Australians with breast, colorectal, non-small cell lung and prostate cancers by linking their cancer registry records with hospital admission and death records 13…”
Section: Introductionmentioning
confidence: 99%